2021
DOI: 10.3390/ijms22094919
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Profiling of the WOX Gene Family in Citrus sinensis and Functional Analysis of a CsWUS Member

Abstract: WUSCHEL-related homeobox (WOX) transcription factors (TFs) are well known for their role in plant development but are rarely studied in citrus. In this study, we identified 11 putative genes from the sweet orange genome and divided the citrus WOX genes into three clades (modern/WUSCHEL(WUS), intermediate, and ancient). Subsequently, we performed syntenic relationship, intron-exon organization, motif composition, and cis-element analysis. Co-expression analysis based on RNA-seq and tissue-specific expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 97 publications
2
16
0
Order By: Relevance
“…To explore the phylogenetic relationship and evolutionary pattern of WOX genes in kiwifruit, the neighbor-joining (NJ) tree was constructed using the full-length protein sequences of the identified 17 AcWOXs , 10 AeWOXs , and previously published 15 AtWOXs and 10 OsWOXs ( WOX genes from Arabidopsis and rice). Consistent with previous reports in Arabidopsis , rice, and other species ( Nardmann & Werr, 2012 ; Lin et al, 2013 ; Tang et al, 2017 ; Shafique Khan et al, 2021 ), both AcWOXs and AeWOXs were classified into three clades (the ancient clade, the intermediate clade, and the modern/WUS clade) ( Fig. 2 ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…To explore the phylogenetic relationship and evolutionary pattern of WOX genes in kiwifruit, the neighbor-joining (NJ) tree was constructed using the full-length protein sequences of the identified 17 AcWOXs , 10 AeWOXs , and previously published 15 AtWOXs and 10 OsWOXs ( WOX genes from Arabidopsis and rice). Consistent with previous reports in Arabidopsis , rice, and other species ( Nardmann & Werr, 2012 ; Lin et al, 2013 ; Tang et al, 2017 ; Shafique Khan et al, 2021 ), both AcWOXs and AeWOXs were classified into three clades (the ancient clade, the intermediate clade, and the modern/WUS clade) ( Fig. 2 ).…”
Section: Resultssupporting
confidence: 89%
“…The WOX gene family is the core regulator for forming the shoot apical meristem and embryonic development, stem cell maintenance, and various other developmental processes in plants ( Ariel et al, 2007 ; Wu, Chory & Weigel, 2007 ; Deveaux et al, 2008 ; Shimizu et al, 2009 ; van der Graaff, Laux & Rensing, 2009 ; Palovaara et al, 2010 ). Genome-wide identification of the WOX gene family had been accomplished in several plants ( Deveaux et al, 2008 ; Liu et al, 2014b ; Cheng et al, 2014 ; Tang et al, 2017 ; Rahman et al, 2017 ; Li et al, 2018 , 2020 ; Ramkumar et al, 2018 ; Shafique Khan et al, 2021 ). However, genome-wide characterization of the WOX gene family had not been conducted in kiwifruits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that WOX genes play different roles in the development of rice roots, stems, and leaves ( Li et al, 2012 ; Wang et al, 2017 ; Zhou et al, 2017 ). The WOX6 gene plays a significant role in the regulation of seed development, especially for the growth and development of seeds under water-deficient conditions ( Shafique Khan et al, 2021 ). In particular, WOX6 gene in rice regulates the asymmetric expression of auxin, resulting in the appearance of rice tiller horns ( Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%